Novel shoreline cap for controlling sheen and dissolved‐phase constituent discharge. Issue 2 (28th February 2020) - Gentry, Jeff L.; Salter‐Blanc, Alexandra; Sheets, Keith; Sharma, Bhawana; Tochko, Laura; Martin, Scott
Abstract: A novel, multilayered shoreline cap was designed and installed to mitigate the release of petroleum light nonaqueous phase liquid (LNAPL) and dissolved‐phase groundwater constituents to the Willamette River in Portland, OR. Releases of LNAPL related to upland impacts caused occasional sheens on a portion of the river within the Portland Harbor Superfund Site. The frequency and volume of sheens decreased following the installation of an upland sheet pile barrier wall, but occasional sheens related to LNAPL impacts stranded downgradient of the wall continued–prompting the design of a shoreline remedy. Because the site is located within the Portland Harbor Superfund Site, the cap was designed to mitigate sheen and to meet the objectives specified in the Portland Harbor Record of Decision including limiting the discharge of certain dissolved‐phase constituents of interest. The cap design was the first instance of combining an oleophilic bio‐barrier to mitigate sheen and an activated carbon layer to capture dissolved‐phase constituents. No sheens have been visually observed since cap installation.